Selective Counteroffers - Barron, John M.; Berger, Mark C.; Black, Dan A. (Journal of Labor Economics, 2006)
The existence of counteroffers can lead to a variety of important labor‐market features. This article develops a model of the selective use of counteroffers in which a firm decides whether to extend counteroffers after a worker informs the firm of an alternative offer. We outline factors that can influence the employer’s net value of making a counteroffer and, thus, affect the likelihood of a counteroffer. We provide a new empirical analysis that examines whether proxies for these factors do, in fact, influence the likelihood that a firm would consider a counteroffer to an employee with a competing offer.